Women Musicians of Uzbekistan : From Courtyard to Conservatory - Merchant, Tanya (Book collections on Project MUSE., 2015)
Influences by women's distinct influence on Uzbekistan's music, this work ventures into Tashkent's post-Soviet music scene to place women musicians within the nation's evolving artistic and political arenas. Drawing on fieldwork and music study carried out between 2001 and 2014, the text challenges the Western idea of Central Asian women as sequestered and oppressed. Instead, the work notes the ways Uzbekistan's women stand at the forefront of four prominent genres: maqom, folk music, Western art music, and popular music.